Virtue as Adventure and Excess : Intertextuality, Masculinity, and Desire in the Twilight Series - Lindén, Claudia (My University, 2013)
The vampire is still primarily a literary figure. The vampires we have seen on TV and cinema in recent years are all based on literary models. The vampire is at the same time a popular cultural icon and a figure that, especially women writers, use to problematize gender, sexuality and power. As a vampire story the Twilight series both produces and problematizes norms in regard to gender, class and ethnici-ty. As the main romantic character in Twilight, Edward Cullen becomes interesting both as a vampire of our time and as a man. In a similar way as in the 19th century novel the terms of relationship are negotiated and like his namesake Edward Rochester, Edward Cullen has to change in important ways for the “happy end-ing” to take place. In spite of a strong interest in sexuality and gender norms in relation to vampires very few studies have focused exclusively on masculinity. This article examines the construction of masculinity in relation to vampirism in the Twilight series. It offers an interpretation of Stephenie Meyer’s novels and the character of Edward as part of a broader field of feminist (re-)uses of the vampire in modern literature with its roots in the literary tradition from Austen and the Brontë-sisters as well as from classic Gothic fiction.
Keywords: 306 Kultur und Institutionen; Twilight Series; Stephenie Meyer; masculinity; vampires; werewolves; Midnight Sun; Jane Austen; Pride and Prejudice; Charlotte Brontë; Jane Eyre; feminist theory; queer theory; gothic